Validating anti-inflammatory and cytotoxic properties of Fagonia cretica L. through metabolic, in vitro, and in silico profiling - Enas I. A. Mohamed; Ahlam H. Elwekeel; Dalia El Amir Mohamed; Mohamed A. Zaki; Marwa H. A. Hassan (BMC Complementary Medicine and Therapies)
Abstract Background Fagonia cretica L. (Family: Zygophyllaceae), is a wild shrub mostly found in Mediterranean districts and extensively used in folk medicine for a vast array of purposes such as antidiabetic and anticancer during the early stages. The goal of the current study was to validate the antioxidant, anti-inflammatory, and cytotoxic properties of Egyptian F. cretica using in vitro studies, metabolic profiling, and in silico approaches. Methods The plant was collected from the Egyptian desert and the alcoholic extract was prepared from its aerial parts, total phenolic and total flavonoid contents were evaluated spectrophotometrically. Antioxidant potential was assessed via 1,1 diphenyl-2-picrylhydrazyl (DPPH) scavenging activity. Anti-inflammatory activity was validated through in vitro COX-2, COX-1, and nitric oxide inhibition. Cytotoxicity was tested against liver (HepG2), breast (MCF-7), and intestinal (CACO2) carcinoma cell lines followed by assessment of its impact on the levels of apoptotic markers namely topoisomerase I and caspase 9 enzymes. Chemical profiling of the extract was performed using LC-HRMS technique. Saponin rich extract was prepared and tested for affecting topo I and caspase 9 enzymes. In silico studies were conducted on anti-inflammatory (COX-2 and COX-1) and cytotoxicity (topoisomerases I, IIα, and IIβ) targets using Autodock vina in PyRx platform. Results Total phenolic and total flavonoid content of the extract were 2.4 ± 0.12 mg GAE/g and 0.18 ± 0.01 mg RE/g, respectively. In vitro results revealed antioxidant activity calculated as 1.4 ± 0.1 mg AEAC/g. In vitro anti-inflammatory assays unveiled inhibition of COX-2 and COX-1 enzymes with IC50 values of 13.02 ± 0.61 and 26.51 ± 0.83 µg/ml, respectively and nitric oxide with IC50 of 147.05 ± 9.61 µg/ml. Cytotoxicity on MCF-7, HepG2, and CACO2 cell line with IC50 values of 6.9 ± 0.53, 7.6 ± 0.42, and 9.2 ± 0.35 µg/ml, respectively, in addition to in vitro topoisomerase I inhibition (IC50 = 13.57 ± 0.71 µg/ml) and caspase 9 induction by 5.66 folds. Metabolic profiling using LC-HRMS technique resulted in dereplication of 21 compounds including triterpenoid saponins, flavonoids, diterpenoids, etc. Interestingly, saponin rich fraction and non-saponin fraction exhibited similar effects on topoisomerase I and caspase 9. In silico investigation unveiled high binding affinities of almost all the detected metabolites to the active sites of COX-2, COX-1, topo I, IIα, and IIβ enzymes. Conclusion Collectively, we can conclude that F. cretica is a new source of many phytochemicals, and a significant natural source as cytotoxic and anti-inflammatory agent.